2012
DOI: 10.1371/journal.pone.0051690
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Facilitate Coal Tar Pitch Extract-Induced Tumorigenic Transformation of Human Bronchial Epithelial Cells Mediated by NF-κB

Abstract: ObjectiveChronic respiratory inflammation has been associated with lung cancer. Tumor-associated macrophages (TAMs) play a critical role in the formation of inflammation microenvironment. We sought to characterize the role of TAMs in coal tar pitch extract (CTPE)-induced tumorigenic transformation of human bronchial epithelial cells and the underlying mechanisms.MethodsThe expression of TAMs-specific CD68 in lung cancer tissues and paired adjacent tissues from cancer patients was determined using immunostainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…16 Moreover, the carcinogenesis effect of TAM has been proved to be related to activation of NF-kB pathway. 17 According to the canonical NF-kB pathway cascade, 11 the phosphorylated IkB kinase (IKK) can further phosphorylate IkB, which is the cytoplasmic inhibitor of the NF-kB complex. When phosphorylated, IkB undergoes ubiquitination and proteasome-mediated degradation rapidly, resulting in the release and nuclear translocation of the NF-kB complex.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, the carcinogenesis effect of TAM has been proved to be related to activation of NF-kB pathway. 17 According to the canonical NF-kB pathway cascade, 11 the phosphorylated IkB kinase (IKK) can further phosphorylate IkB, which is the cytoplasmic inhibitor of the NF-kB complex. When phosphorylated, IkB undergoes ubiquitination and proteasome-mediated degradation rapidly, resulting in the release and nuclear translocation of the NF-kB complex.…”
Section: Introductionmentioning
confidence: 99%
“…In established tumors, TAMs secret factors that promote tumor growth, angiogenesis and metastatic spread of cancer cells, TAMs infiltrated in the invasive front are associated with improvement in hepatic metastasis in colon cancer (Zhou et al, 2010); and TAMs could provide a favorable microenvironment for non-small lung cancer invasion and progression (Wang et al, 2011). In our previous study, we observed that the expression levels of CD68+ TAMs were increased in adjacent lung tumor tissue from lung cancer patients and correlated with lung cancer progression and metastasis (Feng et al, 2012). In the present study, we evaluated the role of macrophages on the promotion of lung cancer progression and metastasis using a nude mice model and the mechanisms involved.…”
Section: Discussionmentioning
confidence: 96%
“…Increasing evidence shows that TAMs have tumor-promotion function. In the pre-tumor stage, inflammatory cytokines and chemokines produced by TAMs can contribute to carcinogenesis transformation (Utrera- Barillas et al, 2010;Feng et al, 2012;Techasen et al, 2012). Infiltrating TAMs could produce a proliferation inducing ligand (APRIL) by direct stimulation with Helicobacter pylori (Hp) to promote the initiation of gastric lymphoma (Munari et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations